2014
DOI: 10.1002/wsbm.1271
|View full text |Cite|
|
Sign up to set email alerts
|

Large scale molecular simulations of nanotoxicity

Abstract: The widespread use of nanomaterials in biomedical applications has been accompanied by an increasing interest in understanding their interactions with tissues, cells, and biomolecules, and in particular, on how they might affect the integrity of cell membranes and proteins. In this mini-review, we present a summary of some of the recent studies on this important subject, especially from the point of view of large scale molecular simulations. The carbon-based nanomaterials and noble metal nanoparticles are the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 81 publications
(93 reference statements)
0
34
0
Order By: Relevance
“…514516 However, in de novo biomedical applications, the cytotoxicity of nanomaterials can also be considered as a therapeutic potential and can be utilized in the killing of cancer cells, and the eradication of bacterial cells, etc. 517 …”
Section: The Protein Corona Effect and Nanotoxicology Of Nps In Biomentioning
confidence: 99%
“…514516 However, in de novo biomedical applications, the cytotoxicity of nanomaterials can also be considered as a therapeutic potential and can be utilized in the killing of cancer cells, and the eradication of bacterial cells, etc. 517 …”
Section: The Protein Corona Effect and Nanotoxicology Of Nps In Biomentioning
confidence: 99%
“…With the increasing applications of nanomaterials in practice, there are growing concerns on their potential biosafety (Ge et al 2008(Ge et al , 2011a(Ge et al , b, 2012aJimenez-Cruz et al 2014;Laurent et al 2013b;Mortensen et al 2013;Pan et al 2012;Rivera-Gil et al 2012;Zhao et al 2008;Zhou and Gao 2014;Zhu et al 2015;Zuo et al 2013). When exposed to biofluids, the surface of nanoparticles is immediately adsorbed by the suspending proteins forming the corresponding complexes of the so-called nanoparticle-protein corona, which endow the nanoparticles with new biological identities (Fleischer and Payne 2014a;Lundqvist 2013;Mirshafiee et al 2013;Monopoli et al 2012).…”
Section: Introductionmentioning
confidence: 98%
“…In the case of interactions of peptides with graphitic surfaces, MD simulations have shown that van der Waals interactions play a dominant role in the adsorption process . There is an overall agreement that hydrophobic interactions and π–π stacking also serve as driving forces for adsorption of peptides and proteins on graphene . Thus, the presence of graphene affects peptides conformations and reduces secondary structure stability as compared to the structure in solution .…”
Section: Introductionmentioning
confidence: 99%